2013
DOI: 10.1080/14616734.2013.863734
|View full text |Cite
|
Sign up to set email alerts
|

Infant negative affect and maternal interactive behavior during the still-face procedure: the moderating role of adult attachment states of mind

Abstract: The current study examined associations between attachment state of mind measured prenatally (N = 259) and maternal behavior in the reunion episode of the still-face procedure when infants were six months of age both as a main effect and in conjunction with infant negative affect. Using a dimensional approach to adult attachment measurement, dismissing and preoccupied states of mind were negatively associated with maternal sensitivity, and each correlated with distinct parenting behaviors. Positive association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
5
20
0
Order By: Relevance
“…Interestingly, the means and the pattern of findings for Unresolved classifications were similar to the Preoccupied pattern. This is consistent with Haltigan et al (2014) who noted in their examination of mean scores that mothers with Preoccupied and Unresolved classifications showed higher levels of intrusive behavior when interacting with their infant in the still-face paradigm than mothers with Dismissing or Autonomous Classifications. In the current study, the similarity in mind-mindedness between Preoccupied and Unresolved could be reflective of the high number of mothers with secondary classifications of Preoccupied in the Unresolved sample (67%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, the means and the pattern of findings for Unresolved classifications were similar to the Preoccupied pattern. This is consistent with Haltigan et al (2014) who noted in their examination of mean scores that mothers with Preoccupied and Unresolved classifications showed higher levels of intrusive behavior when interacting with their infant in the still-face paradigm than mothers with Dismissing or Autonomous Classifications. In the current study, the similarity in mind-mindedness between Preoccupied and Unresolved could be reflective of the high number of mothers with secondary classifications of Preoccupied in the Unresolved sample (67%).…”
Section: Discussionsupporting
confidence: 90%
“…Our provision of a verbal label of their infant's emotional state in the task instructions may have impacted on their performance, by providing them with an emotional label to anchor their imaginal verbal interaction with their infant and resulting in increased use of emotion terms as a means of coping with any distress that arose. This is consistent with research that has highlighted the emotional communication style of mothers with Preoccupied attachments as reflecting heightened levels of negative affect (Cassidy, Sherman, & Jones, 2012) and an intrusive style (Haltigan et al, 2014;Whipple et al, 2011), which may reflect decreased accurate attunement to the needs and state of the infant. Similarly, differences between Autonomous and Dismissing may be more apparent in experimental paradigms that assess for accurate interpretation of infant emotion in concert with emotion term use.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The second aim was to examine the degree to which the attachment states of mind of internationally adoptive and foster parents differ from those of poverty/CPS-referred parents and low-risk parents. After controlling for parental age, sex, ethnicity, and socioeconomic status, (a) internationally adoptive parents had lower scores on the dismissing dimension than the sample of community parents described by Haltigan, Leerkes, Supple, and Calkins (2014); (b) foster parents did not differ from community parents on either the dismissing or the preoccupied AAI dimension; and (c) both internationally adoptive and foster parents had lower scores on the preoccupied dimension than poverty/CPS-referred parents. Analyses using the traditional AAI categories provided convergent evidence that (a) internationally adoptive parents were more likely to be classified as having an autonomous state of mind than low-risk North American mothers based on Bakermans-Kranenburg and van IJzendoorn’s (2009) meta-analytic estimates, (b) the rates of autonomous states of mind did not differ between foster and low-risk parents, and (c) both internationally adoptive and foster parents were less likely to be classified as having a preoccupied state of mind than poverty/CPS-referred parents.…”
mentioning
confidence: 88%
“…So far, organized insecure attachment strategies were closely linked to depression per se, its duration and severity (Conradi and de Jonge 2009;McMahon et al 2008), and the occurrence of postpartum depression (Bifulco et al 2004;Ikeda et al 2014). Moreover, an association of insecure adult attachment with lower quality of relationship to the baby (Rholes et al 1995;Wilkinson and Mulcahy 2010) and less adequate parenting behavior (Bifulco et al 2009;Haltigan et al 2014) was reported. The role of dual/disorganized attachment for the maternal subjective relationship to the baby has not yet been examined.…”
Section: Introductionmentioning
confidence: 96%